Intentionality in the Supplications of Nahj al-Balagha: A Study in the Light of Text Linguistics - الخفاجي, مؤيد جاسم محمد; عبدالامير, سمير سليم (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This study analyzes the intentional structure in the supplications of Imam Ali (peace be upon him) found in Nahj al-Balagha, in light of textual linguistics and within the theoretical framework provided by De Beaugrande and Dressler’s model of textuality standards, with a focus on the standard of intentionality. The study aims to uncover the mechanisms of intentional structuring in these supplications by employing tools from pragmatic linguistics, such as Grice’s Cooperative Principle, Jakobson’s functions of language, and the communicative dimension of cognitive pragmatics as presented by van Dijk. The research is divided into three main sections: the first outlines the theoretical framework of intentionality, defining it as a central component in the realization and effectiveness of a text, and reviews key Western and Arab linguistic efforts that have shaped this concept. The second section is dedicated to the analysis of selected examples of Imam Ali’s supplications—such as the supplication for forgiveness and intimate confessions—from a textual linguistic perspective, showing that these texts go beyond devotional function and are grounded in deep reformative, educational, and critical intentionalities. The third section discusses the relationship between intentionality and reception contexts, emphasizing the interactive nature of the supplicatory text and its capacity to foster spiritual and cognitive communication with the recipient. The findings reveal that the supplications in Nahj al-Balagha are consciously intentional texts governed by pragmatic references. They demonstrate an intertwining of religious expression and rhetorical-communicative depth. These texts represent a complex pragmatic discourse that interacts with the cultural and social context and activates moral and pedagogical intentions as integral components of the supplication's fabric. Accordingly, this study opens new horizons for reading the Arab-Islamic heritage from a textual-linguistic perspective, restoring the significance of intentionality in religious discourse beyond superficial traditional interpretations.